Sickle Cell Disease Pain and Common Chronic Complications - Psalm Duniya Inusa, Baba (IntechOpen, 2016)
This book addresses a wide range of clinically relevant topics and issues in sickle cell disease. This is written by experts in their own field offering a robust, engaging discussion about the presentations and mechanisms of actions in the multiple complications associated with sickle cell disease. This first of the series addresses pain, which is considered the hallmark of sickle cell presentation. It looks at the basic mechanism of pain in sickle cell disease. A more detailed review of precision medicine gives a clear well laid out presentation that is incisive and yet gives in-depth detail relevant to both the clinician and the researcher in the basic laboratory. The same pattern is shown in the discussion on respiratory, cardiac and neurological complications. The 14 chapters also include an overview of sickle cell disease especially in the paediatric age. The content is organized into well-designed broad sections on overview regarding diagnosis including point of care and the role of digital apps in patient management. A key aspect of the book is the opportunity it affords expert physicians to express well-reasoned opinions regarding complex issues in sickle cell disease. The readership would find that it provides a well-described, concise and immediate applicable answers to complex questions. This is highly recommended for scientists and clinicians alike.